Alphakids: veronica who lived in a vinegar bottle - Whiting, Sue (Horwitz Education St. Leonards, NSW, 2003)
"Veronica who lived in a vinegar bottle" sounds like the beginning of a whimsical tale! It evokes a vivid image of a character with a unique living situation. Would you like to explore the story further? Perhaps we can imagine how she came to live there, her adventures, or the friends she made along the way!